ANALYZING PRAGMATICS THROUGH MUSE’S SONG - Atik Muhimatun Asroriyah; Irma Nurhana (Nusantara Hasana Journal, 2022)
This study examines pragmatics, namely speech acts in the lyrics of several songs belonging to MUSE. This study aims to describe the speech acts contained in the lyrics of the song. This study uses a qualitative descriptive method by describing the results of the analysis of the speech acts in the songs belonging to MUSE. The data collected is in the form of text that has been classified by category. The theory used is pragmatics and speech acts. The results of this study indicate that there are several categories of speech acts contained in the lyrics of the songs. The results of this study are as follows, from several song lyrics analyzed there are differences and also similarities in speech act categories between song lyrics with one another. The use of speech acts found in the lyrics include representative/assertive, directive/impositive, expressive/evaluative, commissive, and also declarative/establisif/isbati.